Optimizing Role and Synergy of Indonesian National Police for Handling Prevention of Covid-19 Spread: A Case Study in Human Resource Development Perspective - Dimas Agung Trisliatanto; Anis Byarwati; Sri Iswati; Arif Rahman Nurdianto; Fery Setiawan; Heribertus Agustinus Bilo Tena; Hendro Puspito (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The rise in cases of violations and criminal acts handled by the Indonesian National Police during the COVID-19 pandemic recorded 18 cases of hoarding and increasing prices for personal protective equipment and other items. This study aims to describe and describe the optimization and synergy of the Indonesian National Police in handling the prevention of the spread of COVID-19. Method: This study used a qualitative approach with a case study method which is explored and analyzed based on the data and research information obtained. Result: This study showed that the role of Bhayangkara Fostering Public Security and Order of Indonesian National Police as the Development of Public Security and Order can be optimized to educate the public to prevent hoaxes or stigma regarding this corona virus. This synergy between the Indonesian National Police, the Indonesian Army and the Community Health Center is urgently needed to avoid data falsification and vaccine abuse in the community. Conclusion: This study concluded that the Indonesian National Police optimizes the role and synergy collaboratively with the community and the Government by relying on the Sector Police as the basis for early detection of potential security problems in the community, especially related to handling COVID-19.